2021
DOI: 10.1002/berj.3750
|View full text |Cite
|
Sign up to set email alerts
|

School experiences of Children in Need: Learning and support

Abstract: Children in Need (CIN) have received little attention in education circles. These are children who are usually living at home but where there are concerns over their health or development due to abuse or neglect, or they are disabled. Like Children in Care (CIC, who mostly live away), educational attainments for CIN are lower than for the general pupil population, with higher levels of special educational needs. This article draws on additional analysis from a recently completed, mixed methods study into this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 17 publications
1
17
0
1
Order By: Relevance
“…Being looked after by the state is associated with short and long term adversity and is a predictor of poor life outcomes [5]. It is well evidenced that children in state care do less well than their non-looked-after peers in several domains related to health, education and other social outcomes [3,[6][7][8], although much of this disadvantage stems from their pre-care experience rather than from being looked after by local authorities [9]. Therefore understanding determinants and characteristics of outcomes of looked-after children, as well as the journey through the family justice and care system, is important if improvements are to be made and children and young people are provided with the best possible care and opportunities.…”
Section: Introduction/rationalementioning
confidence: 99%
“…Being looked after by the state is associated with short and long term adversity and is a predictor of poor life outcomes [5]. It is well evidenced that children in state care do less well than their non-looked-after peers in several domains related to health, education and other social outcomes [3,[6][7][8], although much of this disadvantage stems from their pre-care experience rather than from being looked after by local authorities [9]. Therefore understanding determinants and characteristics of outcomes of looked-after children, as well as the journey through the family justice and care system, is important if improvements are to be made and children and young people are provided with the best possible care and opportunities.…”
Section: Introduction/rationalementioning
confidence: 99%
“…For most children, the school journey will be one of relative stability and will be characterised by experiences of success. However, navigating the educational system can be problematic for many children, but particularly for those who have experienced early adversity (Berridge et al, 2020). In England, the Department for Education (DfE) annually collates details of pupil attainment in statutory assessments.…”
Section: Education and Care E Xperiencementioning
confidence: 99%
“…It would be logical to account for the attainment gap between care-experienced pupils and the general pupil population by considering the relatively high proportions of children and young people with an identified Special Educational Need. While special educational need status may account for some of the variance, an attainment gap persists (albeit less pronounced) once this is accounted for (Berridge et al, 2020). Participants in the Berridge et al (2020) study identified four main explanations for the discrepancies in educational progress:…”
Section: Education and Care E Xperiencementioning
confidence: 99%
See 1 more Smart Citation
“…Young people may spend short periods or many years in care, leaving through adoption, returning to live with the birth family or when they reach adulthood.Care-experienced people are among the most educationally marginalised of any identifiable social group, both in childhood and in adulthood (Cameron et al, 2018). Typically, they have markedly lower educational outcomes than their peers, as well as a higher propensity to leave education early (for example, for England, see Berridge et al, 2020;Harrison et al, 2023;Sebba et al, 2015). They are also more likely to be formally excluded (Department for Education, 2019;Kothari et al, 2018), forced to change schools (Sebba et al, 2015) or routed into educational pathways that have been traditionally viewed as being 'lower status' (Harrison, 2020;Harrison et al, 2023).The reasons for this marginalisation are complex and multidimensional.…”
mentioning
confidence: 99%